CHARACTERISTICS OF THE FOVEAL MICROVASCULATURE IN CHILDREN WITH MARFAN SYNDROME: An Optical Coherence Tomography Angiography Study. Issue 1 (4th January 2022) - Chen, Hui; Ng, Kit Yee; Li, Songshan; Jin, Guangming; Cao, Qianzhong; Lian, Zhangkai; Luo, Xiaoling; Ding, Xiaoyan; Zheng, Danying
Abstract : In this study, we found the vessel density and foveal avascular zone circularity index of superficial microvascular plexuses were significantly decreased in children with Marfan syndrome in comparison to the controls. Alterations of microvascular flow are associated with visual acuity, central macular thickness, aortic diameters, and left ventricular ejection fraction. Abstract : Purpose: To investigate the characteristics of foveal microvasculature in children with Marfan syndrome (MFS). Methods: Ninety eyes from 45 MFS patients and 76 eyes from 38 healthy individuals of age-matched, sex-matched, and axial length-matched were enrolled. Characteristics of the superficial capillary plexus including the vessel density, perfusion density, and foveal avascular zone were analyzed by optical coherence tomography angiography. Results: The vessel density and the circularity index of the foveal avascular zone were significantly decreased in the MFS group compared with the controls ( P = 0.017 and P = 0.004 respectively). In MFS group, the central vessel density ( P = 0.003) and perfusion density ( P = 0.001) were negatively correlated with the best-corrected visual acuity. The foveal avascular zone area was correlated with the aortic diameters ( P = 0.001) and the paratemporal perfusion density was correlated with the ejection fraction ( P = 0.003). Moreover, the paratemporal perfusion density and the circularity index of foveal avascular zone were found to be correlated with the aortic Z-score ( P < 0.001 and P = 0.003 respectively). Conclusion: Retinal microvascular decrease and its correlation with best-corrected visual acuity and cardiac functions were observed in the MFS group. The optical coherence tomography angiography may help to characterize the underlying pathophysiology features of MFS and enable early detection and prevention of vascular changes in MFS.